Expression of female sex hormone receptors and its relation to clinicopathological characteristics and prognosis of lung adenocarcinoma - Jin Hwan Lee; Han Kyeom Kim; Bong Kyung Shin (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background Adenocarcinoma (ADC) of the lung exhibits different clinicopathological characteristics in men and women. Recent studies have suggested that these differences originate from the expression of female sex hormone receptors in tumor cells. The aim of the present study was to evaluate the immunohistochemical expression of female sex hormone receptors in lung ADC and determine the expression patterns in patients with different clinicopathological characteristics. Methods A total of 84 patients with lung ADC who underwent surgical resection and/or core biopsy were recruited for the present study. Immunohistochemical staining was performed for estrogen receptor α (ERα), estrogen receptor β (ERβ), progesterone receptor (PR), epidermal growth factor receptor (EGFR), EGFR E746-A750 del, and EGFR L858R using tissue microarray. Results A total of 39 (46.4%) ERα-positive, 71 (84.5%) ERβ-positive, and 46 (54.8%) PR-positive lung ADCs were identified. In addition, there were 81 (96.4%) EGFR-positive, 14 (16.7%) EGFR E746-A750 del-positive, and 34 (40.5%) EGFR L858R-positive cases. The expression of female sex hormone receptors was not significantly different in clinicopathologically different subsets of lung ADC. Conclusions Expression of female sex hormone receptors is not associated with the prognosis and clinicopathological characteristics of patients with lung ADC.